Impact of matrix support on older adults in primary care: randomized community trial - Luciana Colares Maia; Thomaz de Figueiredo Braga Colares; Edgar Nunes de Morais; Simone de Melo Costa; Antônio Prates Caldeira (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To analyze the effect of matrix support on health for older adults in primary care according to the dimensions of frailty measured with the Clinical-Functional Vulnerability Index-20 (IVCF-20). METHODS This is a randomized controlled community trial, developed in the Northern Minas Gerais state, Brazil, in 2018. Initially, the stratification of clinical and functional vulnerability of older adults supported by six Family Health Strategy teams occurred with the IVCF-20. Subsequently, three teams were drawn to receive matrix support for six months, and the others for control. In this intervention, face-to-face educational activities were developed for health teams. Descriptive statistics were performed, followed by bivariate analysis by Pearson's chi-square test, to compare the variables of the IVCF-20 between the two moments (before and after the intervention), with a 5% significance level. Relative risks and respective 95% confidence intervals (95%CI) were estimated. RESULTS The groups were similar before intervention, and the effect of matrix actions was positive for most dimensions measured by IVCF-20 (instrumental daily living activity, cognition, mood, mobility, communication, and multiple comorbidities). At the end of the research, the percentage of frailty in the group assisted by professionals participating in matrix support was lower than that of the control group. CONCLUSIONS Matrix support actions, such as pedagogical attribution and horizontal care for health teams, have the potential to contribute to the articulation of models of care for older adults. REBEC registro BR-7b9xff